Non-coding RNAs in diseases with a focus on osteoarthritis - Pekáčová, Aneta; Baloun, Jiří; Švec, Xiao; Šenolt, Ladislav (Wiley interdisciplinary reviews. RNA, 2023)
Osteoarthritis (OA) is a frequent musculoskeletal disorder affecting millions of people worldwide. Despite advances in understanding the pathogenesis of OA, prognostic biomarkers or effective targeted treatment are not currently available. Research on epigenetic factors has yielded some new insights as new technologies for their detection continue to emerge. In this context, non-coding RNAs, including microRNAs, long non-coding RNAs, circular RNAs, piwi-interacting RNAs, and small nucleolar RNAs, regulate intracellular signaling pathways and biological processes that have a crucial role in the development of several diseases. In this review, we present current knowledge on the role of epigenetic factors with a focus on non-coding RNAs in the development, prediction and treatment of OA. This article is categorized under: RNA in Disease and Development > RNA in Disease.
Keywords: RNA, Circular; Osteoarthritis; Piwi-interagující RNA; Humans; MicroRNAs; lidé; osteoartróza; RNA, Long Noncoding; Piwi-Interacting RNA; RNA dlouhá nekódující; mikro RNA; kruhová RNA